Biosynthesis of the Sesquiterpene Antibiotic Albaflavenone in Streptomyces coelicolor A3(2) - Zhao, Bin (American Society for Biochemistry and Molecular Biology, 2008)
Cytochrome P450 170A1 (CYP170A1) is encoded by the sco5223 gene of the Gram-positive, soil-dwelling bacterium Streptomyces coelicolor A3(2) as part of a two-gene cluster with the sco5222 gene. The SCO5222 protein is a sesquiterpene synthase that catalyzes the cyclization of farnesyl diphosphate to the novel tricyclic hydrocarbon, epi-isozizaene (Lin, X., Hopson, R., and Cane, D. E. (2006) J. Am. Chem. Soc. 128, 6022–6023). The presence of CYP170A1 (sco5223) suggested that epiisozizaene might be further oxidized by the transcriptionally coupled P450. We have now established that purified CYP170A1 carries out two sequential allylic oxidations to convert epi-isozizaene to an epimeric mixture of albaflavenols and thence to the sesquiterpene antibiotic albaflavenone. Gas chromatography/mass spectrometry analysis of S. coelicolor culture extracts established the presence of albaflavenone in the wild-type strain, along with its precursors epi-isozizaene and the albaflavenols. Disruption of the CYP170A1 gene abolished biosynthesis of both albaflavenone and the albaflavenols, but not epi-isozizaene. The combined results establish for the first time the presence of albaflavenone in S. coelicolor and clearly demonstrate that the biosynthesis of this antibiotic involves the coupled action of epi-isozizaene synthase and CYP170A1.